Training on Processing Shellfish Waste into Handicraft Products and Paving Blocks for Youth in The Tambak Oso Sidoarjo - Dyan Agustin; Okik Hendriyanto; Erwin Djuni (Future Science)
Tambak Oso Village is a village that produces milkfish, shrimp and shellfish processed products. During this time in the processing process produces waste / garbage, especially in processed shellfish. The remainder of the shells are only thrown away and have not been utilized, causing environmental problems. With the technology of processing scallops into handicraft products and paving blocks, the problem of scallop shell waste can be overcome. The training is focused on young men and women who are members of the youth group and CV Krishna as a shell-producing SME producing shellfish from processed food production. The method used is divided into 3 stages, the first is counseling about the potential and market opportunities of handicraft products and paving blocks from shell shell waste and shows a good design for handicraft products made from shells to explore creativity. The second is product manufacturing training which is divided into 2 groups, young women are trained in making handicraft products, while young men are trained in making paving block products. In the third stage marketing training is held both online and online so that their products can be introduced and marketed to the wider community. From the results of training in young women obtained several craft designs from shells including decorative mirrors, wall hangings and accessories. Whereas in the training of paving blocks with shell material, a number of paving designs with a high degree of flexibility are found in the form of trapezium so as to produce a more diverse design of paving compositions. With this community service, it can overcome the problem of waste / shellfish shells in Tambak Oso Village, Sidoarjo, and can empower and improve the skills of youth cadets in the village so that it can increase the income of teenagers and reduce unemployment and make the village of Oso Tambak better known and later can be a tourist village.